Investigation of perfluorosulfonic acid ionomer solutions by 19f NMR and DLS: Establishment of an accurate quantification protocol. Issue 21 (19th July 2016) - El Kaddouri, Assma; Perrin, Lara; Jean, Bruno; Flandin, Lionel; Bas, Corine
ABSTRACT: Long side chain perfluorosulfonic acid (PFSA) aqueous solutions with various degrees of substitution and trifluoroacetic acid solutions were investigated by liquid 19 F nuclear magnetic resonance (NMR) to propose a new and efficient quantification protocol. These two examples were selected to respond to a specific need for quantification in fuel cell applications. Classical quantification revealed a systematic underestimation of the PFSA concentrations at room temperature, in contrast to small fluorinated molecules. Dynamic light scattering data suggested the presence of "NMR silent aggregates" up to 50 °C. These aggregates appeared as large particles of about 30 µm in diameter, resulting from the agglomeration of primary aggregates through hydrogen bonds. An increase of the measurement temperature to 80 °C was sufficient to take apart the secondary aggregates, and get the correct quantification. In parallel, a rapid 19 F NMR quantification method was developed using a careful analysis of the Signal‐to‐Noise ratio. This new method provided, in at least a six decades range, an estimation of the PFSA concentration without the need for an external reference. This approach may be successfully applied to determine the fluorine atom content of any small molecule or polymer. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 2210–2222 Abstract : A long perfluorosulfonic acid (PFSA) side chain was used as a proton exchange membrane for a fuel cell application undergoing chemical degradation. NMR spectroscopy could be one powerful technique to quantify degradation though PFSA and derivate products released during FC operation. This work proposes a suitable and new "three step" NMR protocol using signal to noise ratio, as well as showing the aggregation of PFSA impact quantification under a temperature threshold of 80°C.